An application of marital horizon theory to dating violence perpetration - Johnson, Matthew D.; Anderson, Jared R.; Stith, Sandra M. (My University, 2013)
Elements of marital horizon theory (the importance of marriage, desire for marriage now, and beliefs about the ideal age of marriage) were examined in relation to dating violence perpetration using a sample of 611 college students from a large Midwestern university. We examined whether marital horizon variables significantly predicted dating violence perpetration above and beyond other known predictors of dating violence. Results indicate desire to marry was the only element of marital horizon theory to emerge as a significant predictor of dating violence. However, it was only salient for women’s perpetration of psychological aggression. Implications of the findings are discussed, including the possibility that marital horizon theory may be a proxy for conventionality. Future directions for research are discussed.
Keywords: Marital horizon theory; Dating violence